Identification of odour-active compounds of pasteurised orange juice using multidimensional gas chromatography techniques - Mastello, Raíssa Bittar [UNESP]; Capobiango, Michely; Chin, Sung-Tong; Monteiro, Magali [UNESP]; Marriott, Philip J. (My University, 2015)
Odour-active compounds present in pasteurised orange juice were identified by gas chromatography-olfactometry (GC-O) employing heart-cut multidimensional GC techniques with olfactometry (O) and mass spectrometry (H/C MDGC-O/MS) and comprehensive two-dimensional gas chromatography-accurate mass time-of-flight MS (GC×GC-accTOFMS). Headspace solid phase microextraction sampling proved to be qualitatively adequate for the analysis of pasteurised orange juice. The GC-O approach distinguished 13 potent odour regions (detection frequency≥3) in the orange juice extract, in which 7 regions were then subjected to detailed identification of the compounds that contribute to the odour, by using higher resolution H/C MDGC-O/MS. This analysis permitted the odour-active peaks to be better resolved on the 2D column, with removal from background matrix, for the seven regions. GC×GC-FID and GC×GC-accTOFMS reveal the overall complexity of the volatile compounds in the product and assisted in assignment of the isolated peaks of the odour-active compounds, confirming the identification in a number of cases. Four aldehydes (hexanal, heptanal, octanal, citral), 2 esters (ethyl butanoate, methyl hexanoate), and 4 monoterpenes (α-pinene, D-limonene, linalool, α-terpineol) were confirmed in accordance with olfactometry assessment in the processed juice. This multi-assessment instrument approach of GC-O, GC×GC, and H/C MDGC provided an effective insight into the processed orange juice aroma.
Keywords: Aroma; Comprehensive two-dimensional gas chromatography; GC-olfactometry; Multidimensional gas chromatography; Orange juice